Design and research on bending mould of high-strength plates - Zhou Huan; Hui Weidong (КНУБА, 2018)
CNC bending machine is a kind of molding pressure equipment, which is widely used in the process of sheet metal bending, it can press the sheet metal into different angles and different geometric shapes. Equipped with the corresponding industrial equipment, it can also achieve stretching, punching, such as corrugation processing technology. With the development of production technology, people become more and more pursue the quality. High-strength plate tensile strength and hardness is very high, When using a common mould for bending, would first destroy the mould and can't be bending. In this paper, the initial design of high-strength plate bending mold is carried out, the 3D model of each part of the mould is established, and the simulation analysis of the stress is carried out. The bending principle of the mould and the calculation formula of the bending force are introduced, has the very important economic significance for the reasonable selection of bending mould.
Keywords: high-strength plate; mould; bending principle; bending force; 621.74.04